2022
DOI: 10.3389/fphar.2022.1023517
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria-targeted antioxidant SkQ1 inhibits leukotriene synthesis in human neutrophils

Abstract: Leukotrienes are among the most potent mediators of inflammation, and inhibition of their biosynthesis, is becoming increasingly important in the treatment of many pathologies. In this work, we demonstrated that preincubation of human neutrophils with the mitochondria targeted antioxidant SkQ1 (100 nM) strongly inhibits leukotriene synthesis induced by three different stimuli: the Ca2+ ionophore A23187, the chemotactic formyl-peptide fMLP in combination with cytocholasin B, and opsonized zymosan. The SkQ1 anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 81 publications
1
10
0
Order By: Relevance
“…DPI stimulated the accumulation of LTB4 and total leukotrienes ( Figure 1D ). This effect was observed previously when leukotriene synthesis was induced by various stimuli and was attributed to inhibition of LTB4 omega-hydroxylation ( 22 ). In fact, the ratio of LTB4 to ω-LTB4 with DPI is higher, than in other treatments ( Figures 1 , 2 ).…”
Section: Resultssupporting
confidence: 74%
See 4 more Smart Citations
“…DPI stimulated the accumulation of LTB4 and total leukotrienes ( Figure 1D ). This effect was observed previously when leukotriene synthesis was induced by various stimuli and was attributed to inhibition of LTB4 omega-hydroxylation ( 22 ). In fact, the ratio of LTB4 to ω-LTB4 with DPI is higher, than in other treatments ( Figures 1 , 2 ).…”
Section: Resultssupporting
confidence: 74%
“…We have shown that S. typhimurium stimulates 5LOX, but the mechanism of the enhancing effect of bacteria upon subsequent addition of fMLP remains unclear. We have recently shown that LTB4 synthesis induced by fMLP (as well as some other stimuli) is dependent on mtROS production ( 22 ). However, the effect of fMLP in this study was artificially stimulated by cytochalasin, which disrupts the actin cytoskeleton.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations